Reverse design and tests of vegetable plug seedling pick-up mechanism of planetary gear train with non-circular gears - Zhu, Zhifang; Wu, Guohuan; Ye, Bingliang; Zhang, Yongchang (International Journal of Agricultural and Biological Engineering, 2023)
In the previous research, the seedling pick-up mechanism of the planetary gear train with incomplete eccentric circular gear and non-circular gears for vegetable plug seedlings still has two shortcomings. One is that not enough seedling pick-up depth leads to a low success ratio of seedling pick-up at high rotation speeds, the other is that the smaller seedling pushing angle results in poor seedling pushing effect. Therefore, the reverse design of the seedling pick-up mechanism based on its motion trajectory was carried out. The local trajectory of seedling pick-up and seedling pushing sections was adjusted to obtain the theoretical motion trajectory of the seedling pick-up mechanism. The cubic non-uniform B-spline curve was used to fit the adjusted trajectory. A novel seedling pick-up mechanism of the planetary gear train with non-circular gears was proposed, including three combined non-circular gears, four non-circular gears, one planetary carrier, and two seedling pick-up arms. The reverse design model of the mechanism was established. The analysis and design software of the mechanism was developed to obtain the mechanism parameters meeting design requirements. The virtual prototype of the mechanism was established and its physical prototype was manufactured. Through the virtual motion simulation and high-speed photographic kinematics bench tests of the mechanism, the kinematic model and results of reverse design of the mechanism were verified, with the kinematic performances of the mechanism prototype studied. The seedling pick-up tests of the mechanism were conducted in the laboratory. The success ratios of seedling pick-up were 94.2%, 95.6% and 90.2% while the seedling pick-up efficiencies of the mechanism were 60, 80 and 100 plants per minute per row, respectively. Besides, the seedling pushing effect was improved mush because of the greater seedling pushing angle. The seedling pick-up mechanism through revise design is of high value to be applied in the practical vegetable plug seedling transplanters. Keywords: vegetable plug seedling, seedling pick-up mechanism, non-circular gear, reverse design, virtual simulation, seedling pick-up tests DOI: 10.25165/j.ijabe.20231602.7423 Citation: Zhu Z F, Wu G H, Ye B L, Zhang Y C. Reverse design and tests of vegetable plug seedling pick-up mechanism of planetary gear train with non-circular gears, China. Int J Agric & Biol Eng, 2023; 16(2): 96-102.